A Comparative Study of Problem-Posing Implementation Between Indonesia and Abroad in Mathematics Education - Inayah Wulandari; Yuanda Oktrin Lay; Puja Asti Ananta; Abdul Khair Idham Hamzah; Carlos Surya Mahardika Biaf (Journal of General Education and Humanities, 2026)
The application of problem posing in mathematics education faces challenges, including teacher misconceptions and difficulties. This study examines the implementation of problem posing in Indonesia and internationally, focusing on the improvements achieved and the steps taken to achieve them. A Systematic Literature Review (SLR) method with a qualitative descriptive approach was used, adhering to PRISMA guidelines, to explore the impact of problem posing on cognitive and affective aspects. Cognitive aspects include creativity, problem-solving skills, critical thinking, mathematical communication, and related skills, while affective aspects include motivation, curiosity, and enjoyment. The research found that the general structure of problem posing is similar across countries: the teacher presents a situation, students pose a problem, and then solve it. However, international practices often include additional steps, such as identifying problem elements and designing problem structures, before formulation. Indonesia's approach tends to focus more on textbook-based activities and exercises. This study highlights the differences and similarities in problem-posing methods, suggesting that while there are shared principles, international practices often incorporate a more structured and comprehensive approach than those in Indonesia.